2011
DOI: 10.1089/apc.2010.0257
|View full text |Cite
|
Sign up to set email alerts
|

Validating Five Questions of Antiretroviral Nonadherence in a Public-Sector Treatment Program in Rural South Africa

Abstract: Simple questions are the most commonly used measures of antiretroviral treatment (ART) adherence in subSaharan Africa (SSA), but rarely validated. We administered five adherence questions in a public-sector primary care clinic in rural South Africa: 7-day recall of missed doses, 7-day recall of late doses, a six-level Likert item, a 30-day visual analogue scale of the proportion of doses missed, and recall of the time when an ART dose was last missed. We estimated question sensitivity and specificity in detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 54 publications
(54 reference statements)
0
33
0
Order By: Relevance
“…Reviews have shown that self-reported measures range from single items asking for the number of prescribed doses missed in a specified time period to numerous complex items requiring detailed recall; very few studies report using the same self-reported adherence measure, making it difficult to compare results across studies [9, 21, 23]. An analysis in South Africa evaluating the performance of five commonly used self-reported adherence questions found that all questions were poor predictors of virologic and/or immunologic failure [36]. Similarly, another study in Cape Town using a short adherence scale in HIV-infected adults found no correlation between the scale score and having a detectable VL [37].…”
Section: Discussionmentioning
confidence: 99%
“…Reviews have shown that self-reported measures range from single items asking for the number of prescribed doses missed in a specified time period to numerous complex items requiring detailed recall; very few studies report using the same self-reported adherence measure, making it difficult to compare results across studies [9, 21, 23]. An analysis in South Africa evaluating the performance of five commonly used self-reported adherence questions found that all questions were poor predictors of virologic and/or immunologic failure [36]. Similarly, another study in Cape Town using a short adherence scale in HIV-infected adults found no correlation between the scale score and having a detectable VL [37].…”
Section: Discussionmentioning
confidence: 99%
“…101-103 Health workers (including those involved in the care of the control group in a DOT intervention) usually lack direct knowledge of patients’ pill taking behaviour and may thus misestimate true adherence. Objective measurement instruments, such as pharmacy refill data, pill count or medication events monitoring system (MEMS), may not necessarily reflect true pill-taking if patients discard pills or obtain ART from friends, family members, or from pharmacies that are not captured in the refill data.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] The methods of assessing nonadherence are diverse, 8,9 sometimes cumbersome to implement and may not actually correlate with immunologic or virologic failure. 10 In addition, factors associated with nonadherence to ART vary by social, cultural, and local contexts. 11 Studies of the predictors of nonadherence to ART among HIV-positive patients in areas of high HIV/AIDS burden are crucial to determine local factors associated with adherence to ART and to assist with the development and implementation of programs that maximize adherence.…”
Section: Introductionmentioning
confidence: 99%